Health Information Seeking Among University Students Before and During the Corona Crisis—Findings From Germany - Schäfer, Markus; Stark, Birgit; Werner, Antonia M.; Tibubos, Ana Nanette; Reichel, Jennifer L.; Pfirrmann, Daniel; Edelmann, Dennis; Heller, Sebastian; Mülder, Lina Marie; Rigotti, Thomas; Letzel, Stephan; Dietz, Pavel (Frontiers in Public Health, 2021)
Health information-seeking behavior is the process of gathering information about health and disease and can be influential for health-related perception and behavior. University students are an important target group for prevention and health promotion and largely belong to an age group that is considered to play a leading role in propagating the SARS-CoV-2 epidemic in Germany. The paper deals with students' health information-seeking behavior before and during the corona crisis, aiming to give insights into its determinants and implications. Using the example of a large German comprehensive university and based on two cross-sectional surveys in the summer of 2019 (n = 4,351) and 2020 (n = 3,066), we investigate which information channels students use for health information, how information seeking changes during the course of the pandemic, and to what extent information seeking is associated with risk perception and risk behavior. For a subsample of participants that participated in both surveys (n = 443), we also trace developments at the individual level through a longitudinal analysis. The results show that students' health information seeking takes place primarily online and changed markedly during the corona crisis. The comparatively high relevance of sources that are largely based on unchecked user-generated content raises the concern whether students' health information-seeking behavior guarantees the necessary quality and reliability of health information. Significant correlations between the intensity of corona-related information seeking, risk perception, and actual risk behavior were found.